Efficacy and safety of SENS-401 in sudden sensorineural hearing loss: The AUDIBLE-S randomized placebo-controlled phase IIb trial - Braverman, Itzhak; Elziere, Maya; Komazec, Zoran; Cohen-Vaizer, Mauricio; Kalcioglu, Mahmut Tayyar; Chrobok, Viktor; Kazmer, Igor; Hilly, Ohad; Esteve-Fraysse, Marie Jose; Doweck, Ilana; Glotin, Anne-Lise; Fitoussi, Serge; et al. (American journal of otolaryngology, 2024)
PURPOSE: Safety and efficacy of SENS-401, a serotonin type 3 (5-HT3) receptor antagonist and calcineurin inhibitor, in patients with acute sudden sensorineural hearing loss (SSNHL). METHODS: Multicentre randomized, double blind, placebo-controlled trial enrolled adult subjects with sudden sensorineural hearing loss (SSNHL) or unilateral/bilateral acute acoustic trauma leading to SSNHL within 96 h of disease onset. Subjects were randomly assigned to one of the three oral dose groups: 29 mg, 43.5 mg or placebo given twice daily for 28 days. The primary endpoint was the change from baseline in Pure Tone Average (PTA) in the affected ear to the end of treatment visit (day 28). Subjects were further followed up 8 weeks after the end of the treatment period (day 84). RESULTS: A total of 115 subjects were randomized. SENS-401 was well tolerated. Although the primary efficacy endpoint was not met at day 28, post-hoc analyses revealed clinically significant and meaningful efficacy outcomes with SENS-401 when compared to placebo in a substantial group of participants diagnosed with idiopathic SSNHL and who had received corticosteroid treatment. Notable improvements were observed in the PTA change from baseline, the complete hearing recovery rate, and the Word Recognition Score (WRS), particularly at day 84. The responder rate consistently favored treated subjects over those who received the placebo. CONCLUSION: While the primary endpoint was not achieved at the end of the treatment period, the study revealed consistently positive efficacy results of clinical relevance in patients with idiopathic SSNHL who received SENS-401, particularly in the 8-weeks follow-up phase after the completion of the treatment.
Keywords: následné studie; lidé; Middle Aged; výsledek terapie; Adult; Audiometry, Pure-Tone; Female; audiometrie čistými tóny; vztah mezi dávkou a účinkem léčiva; aplikace orální; Humans; Follow-Up Studies; Dose-Response Relationship, Drug; Double-Blind Method; lidé středního věku; mužské pohlaví; mladý dospělý; Administration, Oral; percepční nedoslýchavost; ženské pohlaví; Young Adult; Treatment Outcome; Male; Aged; Hearing Loss, Sensorineural; Hearing Loss, Sudden; dvojitá slepá metoda; dospělí; náhlá nedoslýchavost; senioři